Are some effector systems harder to switch to? In search of cost asymmetries when switching between manual, vocal, and oculomotor tasks. - Hoffmann, Mareike A.; Koch, Iring; Huestegge, Lynn (Memory & Cognition, 2022)
In task-switching studies, performance is typically worse in task-switch trials than in task-repetition trials. These switch costs are often asymmetrical, a phenomenon that has been explained by referring to a dominance of one task over the other. Previous studies also indicated that response modalities associated with two tasks may be considered as integral components for defining a task set. However, a systematic assessment of the role of response modalities in task switching is still lacking: Are some response modalities harder to switch to than others? The present study systematically examined switch costs when combining tasks that differ only with respect to their associated effector systems. In Experiment 1, 16 participants switched (in unpredictable sequence) between oculomotor and vocal tasks. In Experiment 2, 72 participants switched (in pairwise combinations) between oculomotor, vocal, and manual tasks. We observed systematic performance costs when switching between response modalities under otherwise constant task features and could thereby replicate previous observations of response modality switch costs. However, we did not observe any substantial switch-cost asymmetries. As previous studies using temporally overlapping dual-task paradigms found substantial prioritization effects (in terms of asymmetric costs) especially for oculomotor tasks, the present results suggest different underlying processes in sequential task switching than in simultaneous multitasking. While more research is needed to further substantiate a lack of response modality switch-cost asymmetries in a broader range of task switching situations, we suggest that task-set representations related to specific response modalities may exhibit rapid decay.